Easy Ways to Distinguish Data with Interval and Ratio Scales - Heru Santoso Wahito NUGROHO; Joel Rey U. Acob; Angelito E. Alvarado; Wiwin Martiningsih (Health Notions, 2020)
Easy Ways to Distinguish Data with Interval and Ratio Scales